Systematic Characterization of Degraded Anion Exchange Membranes Retrieved from Vanadium Redox Flow Battery Field Tests - Herrmann, Elke (Membranes (Basel), 2021)
Commercially available anion exchange membranes were retrieved from VRFB field tests and their degradation due to the various operation conditions is analyzed by in-situ and ex-situ measurements. Ion exchange capacity, permeability and swelling power are used as direct criteria for irreversible changes. Small-angle X-ray scattering (SAXS) and Differential scanning calorimetry (DSC) analyses are used as fingerprint methods and provide information about the morphology and change of the structural properties. A decrease in crystallinity can be detected due to membrane degradation, and, in addition, an indication of reduced polymer chain length is found. While the proton diffusion either increase or decline significantly, the ion exchange capacity and swelling power both are reduced. The observed extent of changes was in good agreement with in-situ measurements in a test cell, where the coulombic and voltage efficiencies are reduced compared to a pristine reference material due to the degradation process.